Exploring Learners’ Experiences in Video-conference Classrooms through theExtended Technology Acceptance Model (Asean Journal of Engineering Education, 2022)
The forced switch to fully online learning during the pandemic lockdown resulted in the conversion of video-conference platforms into digital classrooms. The emergency situation at the time left no room for necessary research, training and adequate deployment process, thus forcing both learners and instructors to adopt these learning environments as the only solution to learning during those times. After the lockdown seasons were over, several educational institutions have been considering hybrid instructional modes, thereby making these platforms to persist within education. This necessitates the assessment of learners’ perception on learning in these new classrooms. This study aims to inform and inspire the design of inclusive, and sensitive future learning environments and schools where the needs of all types of learners are factored into instructional design and delivery.  An analysis model based on the Technology Acceptance Model (TAM) was deployed in this study which reports on findings from an online survey of 86 respondents consisting of 48 males and 38 females all educated at post-secondary levels. Respondents ages were between 17 and 60 years with a mean age of 30.49 years. Findings show positive learners’ perceptions of video-conference in terms of most constructs, with more neutral and almost negative feedback regarding support for collaboration and instructor presence. No negative perceptions were reported regarding frustration with the technology, and no difference in perception was expressed regarding continuation of virtual learning on video-conference, or return to physical classroom. Platforms were rated by respondents based on factors considered by respondents as important for learning; the highest ratings were assigned based on features including screen sharing, host meeting control capabilities and guest control.
Keywords: Video-conference classroom; Zoom; Post-COVID education; Technology Acceptance Model; TAM; Communication technology